An Exploration of Counselling Interventions and School Education Programs on Bullying Prevention and Treatment - Hasrul, Hasrul; Arif, Nutfah A.M.; Hastiani, Hastiani (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
Research findings on guidance and counseling services and other educational programs on bullying problems in Indonesia have been widely conducted and published. However, efforts to find references on interventions for preventing and treating bullying problems in the city of Ternate through scientific publications are still relatively few or have not contributed much. Therefore, this study explores how much intervention of guidance and counseling services in schools and educational programs (outside of guidance and counseling services) to prevent and handle bullying problems in Ternate City. Methodologically, this study follows the basic idea of ​​narrative literature review (NLR), by referring to five steps of the process. The analysis results describe that in the last five years, the intervention of guidance and counseling services in schools on preventing and treating bullying problems in Ternate City is still minimal because only one published article was found. Meanwhile, educational program interventions (excluding guidance and counseling services) on the problem of bullying in the city of Ternate have been carried out quite a lot with intervention strategies and targets at different educational levels. Thus, these findings indicate that intervention of guidance and counseling services in schools on the prevention and treating of bullying in Ternate City is still very minimal when compared to intervention of other educational programs.